Lactobacillus rhamnosus GG ATCC53103 and Lactobacillus plantarum JL01 improved nitrogen metabolism in weaned piglets by regulating the intestinal flora structure and portal vein metabolites - He, Feng; Jin, Xueying; Wang, Chunfeng; Hu, Jingtao; Su, Shuai; Zhao, Lei; Geng, Tingting; Zhao, Yuan; Pan, Li; Bao, Nan; Sun, Hui (Frontiers in Microbiology, 2023)
At present, most studies have shown that probiotics have a positive regulatory effect on the nutritional metabolism of the body, but the mechanism is still unclear. Here, 48 piglets were divided into four groups. The control group was not fed probiotics, the Lac group was fed L. Rhamnosus GG ATCC53103, the Rha group was fed L. Plantarum JL01, and the mix group was fed two types of probiotics. Nitrogen metabolism and mRNA levels of mTOR and S6K in skeletal muscle were observed in each group. Then, metagenome and non-targeted metabonomics were used to observe the changes of intestinal microorganisms and plasma metabolites in portal channels after probiotics feeding. Finally, we combined the results of omics analysis to reveal the mechanism of probiotics on nitrogen metabolism in weaned piglets. The results showed that L. Rhmnosus GG ATCC53103 and L. Plantarum JL01 increased nitrogen apparent digestibility, nitrogen deposition rate, and nitrogen utilization rate of weaned piglets (P < 0.05); the relative expression of mTOR and SK6 mRNA in skeletal muscle increased significantly (P < 0.05). When L. rhamnosus GG ATCC53103 and L. plantarum JL01 were combined, we found that Clostridium and Prevotella significantly increased in the jejunum (P < 0.05). The relative abundance of Lactobacillus, Ruminococcus, Streptococcus, and Prevotella in the ileum increased significantly (P < 0.05). Compared with the control group, L-Tryptophan, 3-Phosphonyloxypyruvate, cis-Aconitate, and Carbamoyl phosphate were significantly increased in the mixed group portal vein. The result of the combinatorial analysis showed that the significantly increased microorganisms could encode the enzyme genes for the synthesis of L-Tryptophan, 3-Phosphonooxypyruvate, cis-Aconitate, and Carbamoyl phosphate. In summary, our results demonstrated that L. Rhamnosus GG ATCC53103 and L. Plantarum JL01 could stimulate the expression of skeletal muscle protein synthesis genes of weaned piglets by modulating the structure of the gut microbiota and its metabolites, thereby improving nitrogen metabolism in weaned piglets.